Synopsis: Tenure (in)security and agricultural investment of smallholder farmers in Mozambique - Ghebru, Hosaena H. (International Food Policy Research Institute, 2015)
Although it is widely recognized that land tenure security is an integral part of agricultural intensification, there is no single clearly defined and universally applicable property rights regime to achieve this end. Countries that strive for economic development and food security through agricultural intensification need to utilize land governance strategies and policies that fit their context.